Cover Feature: London Dispersion Interactions in Pnictogen Cations [ECl2]+ and [E=E]2+ (E=P, As, Sb) Supported by Anionic N‐Heterocyclic Carbenes (Chem. Eur. J. 71/2018). Issue 71 (6th December 2018) - Ho, Luong Phong; Nasr, Alexandre; Jones, Peter G.; Altun, Ahmet; Neese, Frank; Bistoni, Giovanni; Tamm, Matthias
Abstract : London dispersion interactions contribute essentially to the overall stability of dipnictenes with an [E=E] 2+ (E = P, As, Sb) core supported by anionic N‐heterocyclic carbenes. As illustrated by a dispersion interaction density (DID) plot, extracted from a coupled cluster‐based Local Energy Decomposition (LED) analysis, about half of the dispersion energy stabilization in the dipnictenes results from intramolecular carbene‐carbene interactions. The other half arises from the interaction of the ligands with the E=E moiety. More information can be found in the Full Paper by G. Bistoni, M. Tamm, et al. on page 18922 .